2014
DOI: 10.1007/s00590-014-1548-3
|View full text |Cite
|
Sign up to set email alerts
|

The origin variability of the iliolumbar artery and iatrogenic sciatica

Abstract: The iliolumbar artery (ILA) is a standard branch from the posterior trunk of the internal iliac artery. It is the only pelvic artery ascending from pelvic cavity. Current study comprises 171 cadavers dissection to assess the origin variability of ILA. The present study identified the incidence of the ILA origin variability in Caucasian population which also clarified the iliolumbar variability in males and females. The current study shows that the ILA arises from the common iliac artery in 2%, from the externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…In 0.7 percent of cases, it came from the inferior gluteal artery, as well as the sciatic artery. 12 In our study we have found ILA to be originating from either trunk of IIA or from PD. There were no branches coming from the common iliac or gluteal arteries (Figure 1 Several factors such as genetics, race and tissue vascular demand may have been the cause of such variability.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In 0.7 percent of cases, it came from the inferior gluteal artery, as well as the sciatic artery. 12 In our study we have found ILA to be originating from either trunk of IIA or from PD. There were no branches coming from the common iliac or gluteal arteries (Figure 1 Several factors such as genetics, race and tissue vascular demand may have been the cause of such variability.…”
Section: Discussionsupporting
confidence: 44%
“…Embryologically, the inconsistent origin of ILA may be due to flaw in either the growth or regression of the primitive ILA (plexus). 12 The medial umbilical ligament (superior vesical artery) and the inferior gluteal artery were the two main trunks of IIA during development. The two trunks and the intersection between them are the source of the majority of the branches and any variation in its pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ILA originated from the common iliac artery in 13.33%. Our findings were comparatively lower than the results of Koc T et al (29.4%) [19] but higher than the percent given by the Talalwah et al (2%) [18]. Last and very rare variation i.e.…”
Section: From Posterior Division Propercontrasting
confidence: 82%
“…A study conducted by Teli et al showed that the most common origin of the iliolumbar artery was from the posterior division of IIA proper with the incidence 80% of cases [17]. A similar pattern of origin was observed by Al Talalwah et al with the incidence of 77.9% [18]. The iliolumbar artery arises from posterior division of IIA proper was documented by Naguib et al, Rusu et al in 44% and 32.5% of cases respectively [14,15].…”
Section: From Posterior Division Propermentioning
confidence: 59%
See 1 more Smart Citation